Contributions of Intertextuality to Literary Competence: Traditional Tales in Colombian Elementary School - Perea Insuasty, Pilar; Núñez Delgado, M.ª Pilar (Íkala, Revista de Lenguaje y Cultura, 2024)
One of the central aspects —both in theoretical tenets and classroom practices— of literary education is the attention to the mechanisms that contribute to construction meaning of what is read. Studies on the contributions of working with different versions of folktales suggest that the dialogue between texts contributes to the development of literary competence in childhood. Our research, with a qualitative ethnographic design, was carried out in a group-class of 35 Colombian schoolchildren aged 6-7 years. Its objective is to investigate the effects of the Genettian palimpsestic game on literary competence, which encompasses the critical thinking skills of 6-7 year-old children, based on reading aloud hypertexts and classroom dialogue on two traditional stories, Little Red Riding Hood (hypotextual version of Charles Perrault) and Rapunzel (from the Brothers Grimm).The most outstanding results show that hypertexts generate connections that permeate the cognitive and emotional dimension; that the dialogic approach to the stories also establishes connections with the sociocultural reality of the child reader, and that reading from the intertextual perspective contributes to the structuring of thought patterns that are then applied to the interpretation of other works. The conclusions reaffirm the value of intertextuality to develop literary competence, since it teaches to assume points of view, to expose them and to discuss them based on what has been apprehended with textual frameworks.